Aplikasi Persediaan Barang PT. CAD Solusindo Menggunakan Metode Waterfall - Agus Junaidi; Candra Sumirat (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2018)
The development of media technology in the delivery of information faster and faster and accurate. For that manage information technology is needed either because the information is of great value to a company. The system inventory information is a very important for a company, by implementing a web based information system for running the collection of goods to the company, makes it all work, for data processing of goods, the data became more organized and information about the inventory becomes easier until seen everywhere through the internet. PT. CAD Solusindo is a company engaged in the repair service in communication tools. In the process of recording and calculations performed by PT CAD Solusindo until today still use the program Microsoft Excel, starting from the receipt of goods, goods out and preparing reports addressed to the leader. Designing the system described by UML modeling. The programming language used is PHP and MYSQL database. It is expected that these applications can help the PT. CAD Solusindo to help users to further improve supervision of the stocks held in the company so that the quality of reports resulted more accurately, quickly, and precisely when required as annual audits.